PENGARUH E-COMMERCE TERHADAP PERKEMBANGAN UMKM DI KOTA PALANGKARAYA - Tanti M. Rajagukguk; Hendrik Suryadi, Nadia Anggreani, Indrawan Saputra, Ayu Lestari Doloksaribu (CV. Adiba Aisha Amira, 2024)
This study discusses the influence of e-commerce on the development of Micro, Small, and Medium Enterprises (UMKM) in Palangkaraya City. With the growth of information technology, especially e-commerce, UMKM are undergoing a significant transformation. Although conventional trade still dominates, the shift to e- commerce has affected business dynamics. This study uses a quantitative approach with primary data from 30 UMKM owners who use e-commerce in Palangkaraya. Simple regression analysis showed a relationship between e-commerce and UMKM, but the results were not statistically significant. Nonetheless, UMKM in Palangkaraya City continue to thrive, demonstrating their resilience during difficult times and the potential of utilizing technology for business growth